The Economic Causes and Consequences of Canadian Citizenship - Don J. DeVoretz; Sergiy Pivnenko (Institute for the Study of Labor (IZA), 2004)
Immigrants ascend to citizenship at differential rates in Canada. Why is this so? This paper investigates the economic costs and benefits derived from citizenship to rationalize the differential rates of citizenship ascension. Canadian earnings evidence confirms the sizable economic benefits of citizenship. A decomposition analysis attributes this benefit to selfselection, namely only the more productive immigrants become Canadian citizens.
Keywords: J68; J61; F22; 330; immigration; citizenship; Canada; Staatsangehörigkeit; Migranten; Kosten-Nutzen-Analyse; Kanada